Three-Dimensional Analytical Formula for Oblique and Off-Axis Gaussian Beams Propagating through a Cat-Eye Optical Lens - 赵延仲 孙华燕 喻夏琼 樊萌山 (Chinese physics letters, 2010)
Based on the Collins formula in a cylindrical coordinate system and the method of introducing a hard aperture function into a finite sum of complex Gaussian functions, an approximate three-dimensional analytical formula for oblique and off-axis Gaussian beams propagating through a cat-eye optical lens is derived. Numerical results show that a reasonable choice of the obliquity factor would result in a better focus beam with a higher central intensity at the return place than that without obliquity, whereas the previous conclusion based on geometry optics is that the highest central intensity could be obtained when there is no obliquity.